The Effect of Organizational Support and Organizational Socialization on Affective Commitment: The Mediating Role of Collective Values - Much. Riyadus Solichin; Siti Nur Azizah; Ika Susilowati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of organizational support and organizational socialization on collective values. This study also analyzes the effect of collective values ​​on affective commitment. This study examines the mediating role of collective values ​​in the relationship between organizational support and organizational socialization with affective commitment. This study was conducted using a survey method, 68 respondents who were employees of the Kebumen Wijaya Kusuma Hospital participated in this study. Sampling used convenience sampling method. The method of data analysis was carried out using SEM-PLS with the help of SmartPLS 3 software. The findings of this study indicate that organizational support and organizational socialization are statistically proven to have a positive influence on collective values. The research results also show that collective values ​​have a positive effect on affective commitment. The mediation hypothesis in this study is also proven, namely that collective values ​​mediate the relationship between organizational support and organizational socialization on affective commitment.